What History Can Teach Us about the Future Costs of U.S. Nuclear Power - Hultman, N; Koomey, J; Kammen, D (ASC, 2007)
In response to energy security and environmental concerns, the U.S. is collaborating with nine other countries to develop fourth-generation reactor technology that the industry intended to be safer than current reactors, available at lower total cost, and incurring financial risks no greater than those for other energy technologies. From a three-decade historical database of delivered costs from each of 99 individual U.S. nuclear reactors, we discuss the financial risks for new nuclear power to achieve its cost objectives. We argue that past technology development patterns indicate the importance of including high-cost surprises in the planning process.